(untitled) (Academia Journal of Medicine, 2024)
A good implant integration and long-term favourable clinical outcome are positively correlated with a secure primary (mechanical) stability of the implant. Consequently, in order to guarantee a successful osseointegration, it is crucial to evaluate the initial stability at various time points. This review explores the importance of the primary and secondary implant stability and various tools and instruments to measure the primary implant stability, and also explains about factors affecting the implant primary stability. Dental implant design and its length, diameter, thread depth plays an important role in obtaining the primary implant stability.This review describes different ways to obtain primary stability in compromised bone such aslow density bone and regenerated bone.